The Global Findex Database 2017 : Measuring Financial Inclusion and Opportunities to Expand Access to and Use of Financial Services - Demirgüç-Kunt, Asli (Published by Oxford University Press on behalf of the World Bank, 2021)
The Global Findex database is the world's most comprehensive set of data on how people make payments, save money, borrow and manage risk. Launched in 2011, it includes more than 100 financial inclusion indicators in a format allowing users to compare access to financial services among adults worldwide -- including by gender, age and household income. This third edition of the database was compiled in 2017 using nationally representative surveys in more than 140 developing and high-income countries. The database includes updated indicators on access to and use of formal and informal financial services. It features additional data on Fintech and digital financial services, including the use of mobile phones and internet technology to conduct financial transactions. Global Findex data is utilized to track progress toward the World Bank's goal of Universal Financial Access by 2020 and the United Nation's Sustainable Development Goals. The data also is a source for the G20 Financial Inclusion Indicators and a benchmark for policymakers seeking to expand access to and use of financial services. Lastly, this report discusses opportunities to expand access to financial services among the unbanked, and ways to promote greater use of digital financial services among the underbanked.